2009
DOI: 10.1111/j.1471-4159.2009.06450.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/PI3K signaling protects dentate neurons from oxygen–glucose deprivation in organotypic slice cultures

Abstract: It is known that ischemia/reperfusion induces neurodegeneration in the hippocampus in a sub-region dependent manner. The present study investigated the mechanism of selective resistance/vulnerability to oxygen glucose deprivation (OGD) using mouse organotypic hippocampal cultures. Analysis of propidium iodide uptake showed that OGD induced duration- and sub-region-dependent neuronal injury. As compared to the CA1-3 sub-regions, dentate neuronal survival was more sensitive to inhibition of PI3K/Akt signaling un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 56 publications
0
47
0
Order By: Relevance
“…However, in an in vitro model of ischemia used by Hamabe et al, coincubation of neurons with insulin during 2 h of oxygen-glucose deprivation (as a model of cerebral ischemia) significantly decreased the hypoxia-induced neuronal necrosis [264]. In another study, Sun et al reported that insulin protection against neuronal injury induced by oxygen-glucose deprivation may vary in different subregions of the hippocampus, as the dentate gyrus was reported to be more sensitive to insulin neuroprotection and less vulnerable to ischemia, but CA-1 and CA-3 were reported to be less sensitive to insulin and more vulnerable to ischemia [291].…”
Section: Protective Effects Against Ischemiamentioning
confidence: 99%
“…However, in an in vitro model of ischemia used by Hamabe et al, coincubation of neurons with insulin during 2 h of oxygen-glucose deprivation (as a model of cerebral ischemia) significantly decreased the hypoxia-induced neuronal necrosis [264]. In another study, Sun et al reported that insulin protection against neuronal injury induced by oxygen-glucose deprivation may vary in different subregions of the hippocampus, as the dentate gyrus was reported to be more sensitive to insulin neuroprotection and less vulnerable to ischemia, but CA-1 and CA-3 were reported to be less sensitive to insulin and more vulnerable to ischemia [291].…”
Section: Protective Effects Against Ischemiamentioning
confidence: 99%
“…Currently, direct evidence supporting this notion is limited to in vitro studies. For instance, it has been shown that insulin could protect neurons against a variety of insults, including glucose-oxygen deprivation (Sun et al, 2010), excitotoxicity (Kim and Han, 2005), and oxidative stress (Ribeiro et al, 2014). The neuroprotective action of insulin in vivo, however, remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…This function of PTEN directly antagonizes PI3K to eventually down-regulate AKT (21,22). Several lines of evidence indicated that the AKT signaling pathway responds to oxidative stress (23) and exerts a neuroprotective function (24,25). Moreover, a large number of studies in vitro have illustrated that pharmacological compounds that protect cells against oxidative stress exert their neuroprotective effects through activation of the AKT pathway (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%